What was Killing Babies in Hermoupolis, Greece? An Investigation of Infant Mortality Using Individual Level Causes of Death, 1861–1930 - Michail Raftakis (Historical Life Course Studies)
This paper employs individual level cause of death data from the port city of Hermoupolis on the Greek island of Syros, in order to test the newly-constructed ICD10h coding system. By constructing cause specific death rates for infants from the late 19th century to early 20th century, the paper contributes to a comparative approach, which aims to show how causes of death differ across several locations within Europe and how they develop over time. Given the scarcity of cause of death data both at the individual and aggregate level in Greece roughly prior to the 1920s, the availability of such data in the draft death registers (for sporadic runs of years in the second half of the 19th and early 20th century) and the civil registration (from 1916 onwards) in Hermoupolis provides a deeper understanding of the history of cause-of-death reporting in the country. Infant mortality in Hermoupolis was relatively high throughout the study period, with water-food borne diseases accounting for the highest number of infant deaths, especially during the hot and dry summer months. While the prominent winter peak of neonatal mortality but also congenital-birth disorders could be partially associated with birth seasonality and/or low temperatures over the winter months. Finally, certain vague terms such as 'atrophy' and 'athrepsy', but especially 'drakos' require further investigation until they are firmly understood.